An exploratory analysis of the environmental and social incentives of key management personnel for JSE-listed companies - Haripersadh, Shriya (University of the Witwatersrand, Johannesburg, 2024)
Societal pressure on companies to be environmentally and socially responsible as well as stock exchange requirements have led to the wide adoption of integrated reporting by public companies in South Africa (Baboukardos & Rimmel, 2016; De Villiers et al., 2014; IoDSA, 2016; Lokuwaduge & Heenetigala, 2017; Moloi & Iredele, 2020). The prior literature discusses the importance of remuneration linked to Key Performance Indicators (KPIs). Consequently, analysing whether Key Management Personnel (KMP) have non-financial KPI-linked remuneration provides strong evidence of a company’s commitment to being socially and environmentally responsible. Currently, no research investigates this globally and in the South African context. This study presents a comprehensive comparative analysis of the integration of environmental and social (ES) KPIs in KMP remuneration for South African Johannesburg Stock Exchange listed companies. Data was collected from twenty companies from the JSE’s top, middle and small capitalization companies at different points in time (2011, 2018 and 2022) using content analysis to provide a total sample of 60 companies with 180 firm-years. Data was analyzed using descriptive and inferential statistics. The prevalence, distribution and settlement methods of E, S, and combined ES KPIs in KMP remuneration structures were examined. Utilising both agency theory and stakeholder theory, the research explores how linking the remuneration of KMP to ES KPIs may serve the interests of both shareholders and stakeholders. The findings reveal a progressive adoption of ES KPIs in KMP remuneration structures over the investigated years, with notable variations observed across industries and company size. Larger companies and companies with higher social and environmental impacts utilize more ES KPIs in their remuneration policies. Industry-specific trends influencing the integration of ES KPIs were identified, shedding light on the evolving landscape of corporate governance and sustainability practices. By elucidating the dynamics between KMP remuneration and environmental and social performance metrics, this study contributes to a deeper understanding of how companies incentivise responsible leadership and foster sustainable business practices.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Commerce to the Faculty of Commerce, Law, and Management, School of Accoutancy, University of the Witwatersrand, Johannesburg, 2024
Keywords: Environmental; social; remuneration; KPIs; ES; KMP; incentive; agency theory; stakeholder theory; King IV; Integrated reporting; stakeholders; market capitalization; listing age; industry; CSR; settlement; long-term; short-term; EY Integrated Reporting; SDG-8: Decent work and economic growth